2018
DOI: 10.1007/s00540-018-2469-9
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction rate of patients undergoing sleeve gastrectomy as day-case surgery compared to conventional hospitalization: a prospective non-randomized study

Abstract: Overall satisfaction of patients undergoing SG as day-case surgery was not inferior to that of patients managed by conventional hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…Badaoui et al [19] in their prospective, comparative, evaluation of the satisfaction of general anesthesia of patients undergoing LSG as outpatient (62 patients) and as inpatient (62 patients) based on the EVAN-G questionnaire found a mean score of 66.4 in the outpatient group vs. 68.9 in the inpatient group (not significant difference). In the outpatient group, 19% of patients would have preferred to spend the first night in hospital while in the conventional hospitalization group, 82% of patients would have preferred outpatient management (average length of stay of 1.9 days (1-3)).…”
Section: Mid-term Results and Satisfaction Ratementioning
confidence: 98%
See 1 more Smart Citation
“…Badaoui et al [19] in their prospective, comparative, evaluation of the satisfaction of general anesthesia of patients undergoing LSG as outpatient (62 patients) and as inpatient (62 patients) based on the EVAN-G questionnaire found a mean score of 66.4 in the outpatient group vs. 68.9 in the inpatient group (not significant difference). In the outpatient group, 19% of patients would have preferred to spend the first night in hospital while in the conventional hospitalization group, 82% of patients would have preferred outpatient management (average length of stay of 1.9 days (1-3)).…”
Section: Mid-term Results and Satisfaction Ratementioning
confidence: 98%
“…Only six of these studies were relevant. On these 6 series, there was three single centre retrospective studies [15 -17] , two single centre prospective studies [18,19] and one retrospective, comparative, national database analysis [20] . On these 6 series, two series reported the same population of DCS but one focused on surgical data while the other focused on anaesthesiology data (Table 1).…”
Section: Assessment Of the Quality Of Selected Publicationsmentioning
confidence: 99%
“…In another larger study including more than 130,000 patients, the DC bariatric surgery readmission rate was 4.4% and 2.8% for all patients and those who underwent LSG alone, respectively [33] . Studies that assessed DC-LSG alone reported a readmission rate ranging from 0% to 8.5% [19][20][21]31] , while those that assessed DC-LRYGB alone reported a rate of 1.7-4% [24,25,34] .…”
Section: Discussionmentioning
confidence: 99%
“…The earliest DCS techniques for bariatric surgery used gastric banding [17,18] . The viability and safety of using DCS for LSG [19][20][21][22] , and LRYGB [23][24][25] procedures were been previously discussed and almost established. To date, no studies have investigated such an issue for OAGB.…”
Section: Introductionmentioning
confidence: 99%
“…The sample size was calculated based on our 65-patient pilot test. According to the formula N = Z 2 pq/δ 2 (α = 0.05, δ = 0.07, p = 56%, q = 1-p), [ 21 , 22 ] 193 patients were required for a statistical power of 90% power at the 0.05 significance level. Assuming a 15% dropout rate, 227 patients were deemed for this study.…”
Section: Methodsmentioning
confidence: 99%